Minichromosome maintenance 2 and 5 expressions are increased in the epithelium of hereditary gingival fibromatosis associated with dental abnormalities - Hercílio Martelli-Júnior; Carolina de Oliveira Santos; Paulo Rogério Bonan; Paula de Figueiredo Moura; Carolina Cavalcante Bitu; Jorge Esquiche León; Ricardo D. Coletta (Clinics, 2011)
INTRODUCTION: Gingiva fibromatosis is a relatively rare condition characterized by diffuse enlargement of the gingiva, which is caused by expansion and accumulation of the connective tissue. OBJECTIVE: The aim of the present study was to investigate proliferative and apoptotic biomarker expression in normal gingiva and two forms of gingival fibromatosis. METHODS: Archived tissue specimens of hereditary gingival fibromatosis, gingival fibromatosis and dental abnormality syndrome and normal gingiva were subject to morphological analysis and immunohistochemical staining. The results were analyzed statistically. RESULTS: Proteins associated with proliferation were found in the nuclei of epithelial cells from the basal and suprabasal layers, whereas apoptotic proteins were detected in the cytoplasm of the upper layers of the epithelium. Increased expressions of minichromosome maintenance proteins 2 and 5 were observed in the gingival fibromatosis and dental abnormality syndrome samples. In contrast, geminin expression was higher in normal gingiva samples. No difference in the expression of apoptotic proteins was observed among the groups. CONCLUSION: Our findings support a role for augmented proliferation of epithelial cells within the overgrown tissues associated with gingival fibromatosis or dental abnormality syndrome. However, our data suggest that different biological mechanisms may account for the pathogenesis of different types of gingival fibromatosis.